Features of management accounting accounts receivable and accounts payable - L. G. Danilova (Путеводитель предпринимателя)
The causes of occurrence of debts are reviewed, the classification of debts was given, conditions for the formation of overdue debt are reviewed, risk reduction methods of overdue debts were offered. The recommendations proposed in the article will allow organizations to plan and organize work with receivables and payables.